Building and Managing an Ambidextrous SME - Vogl, Martin (2024)
Over the last few decades, scholars from various research streams have accumulated an extensive body of literature on organizational ambidexterity, its antecedents, modes of balancing, and distinct performance outcomes. However, despite the accumulated research, little remains known about how and under what conditions an ambidextrous orientation is implemented and managed in small and medium-sized enterprises. The current project aims to demonstrate how, and under what conditions, small and medium-sized across Central and Eastern Europe can build and manage ambidexterity. In particular, this project demonstrates how an exploitation-driven insurance firm complemented its core business through exploratory activities to create ambidexterity across geographically dispersed business units. In turn, this project offers a better and more substantial understanding of the dynamic process of how ambidexterity was implemented and managed. We draw on five strategic levers that helped firms do so, which included organizational design, strategic management, technology and innovation, learning and adaptation, and organizational change. Furthermore, we illustrate how capability-shifting and capability-building processes were combined to balance organizational tensions created by exploitation and exploration. Given that the firm’s business units differ in business focus, operations, and necessary capabilities, we discuss which capabilities were shifted and which had to be built to implement and enhance exploratory activities. Finally, we consider an international setting by shedding light on a firm that operates in an international cross-country setting.